2019
DOI: 10.1111/jocd.13139
|View full text |Cite
|
Sign up to set email alerts
|

The Safety and efficacy of botulinum toxin type A injection for postoperative scar prevention: A systematic review and meta‐analysis

Abstract: Background Active prevention and treatment of scars are particularly important. Several studies have used botulinum toxin type A(BTXA) to prevent postoperative scarring. The aim of this systematic review and meta‐analysis was to systematically evaluate the efficacy and safety of BTXA in preventing and treating postoperative scars. Methods A computer‐based search was conducted for the five databases including PubMed, Cochrane Library, EMBASE, CNKI, and Wanfang up to May 22, 2019, to collect the relevant literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
(87 reference statements)
0
13
0
4
Order By: Relevance
“…BTA has been available for clinical use for more than 30 years and its efficacy and safety are well proved. Nowadays, an increasing number of studies have showed that BTA injections inhibit the formation of HS 2‐5 . Moreover, our previously published random clinical trial found that the injection of BTA in the early postoperative could decrease the scar formation, reduce the scar width, and make the overall appearance more satisfactory 6 .…”
Section: Introductionmentioning
confidence: 99%
“…BTA has been available for clinical use for more than 30 years and its efficacy and safety are well proved. Nowadays, an increasing number of studies have showed that BTA injections inhibit the formation of HS 2‐5 . Moreover, our previously published random clinical trial found that the injection of BTA in the early postoperative could decrease the scar formation, reduce the scar width, and make the overall appearance more satisfactory 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies show that BTXA has a significant effect on the prevention of postoperative scars 8,26 . Clinicians have achieved good prophylactic results with BTXA injection near the surgical incision after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…25 Some studies show that BTXA has a significant effect on the prevention of postoperative scars. 8,26 Clinicians have achieved good prophylactic results with BTXA injection near the surgical incision after surgery. Laarakker reported that BTXA is used to salvage ischaemic hand injuries to avoid finger or limb amputation.…”
Section: Comparison Of Vegf Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al 37 performed a meta-analysis in 2016; however, 2 of the studies 38,39 included in this analysis were not RCTs, and the experimental group of 1 study was BTXA combined with intense pulsed light. In 2019, Yang et al 40 conducted a meta-analysis; however, most of the studies included in this analysis were published in Chinese, and no sensitivity analysis was performed. Previous systematic reviews have not reached a consensus on BTXA in the prevention of scarring.…”
Section: Discussionmentioning
confidence: 99%